Broadband field-resolved terahertz detection via laser induced air plasma with controlled optical bias - Li, Chia-Yeh; Seletskiy, Denis V.; Yang, Zhou; Sheik-Bahae, Mansoor (Optics express, 2015)
We report a robust method of coherent detection of broadband THz pulses using terahertz induced second-harmonic (TISH) generation in a laser induced air plasma together with a controlled second harmonic optical bias. We discuss a role of the bias field and its phase in the process of coherent detection. Phase-matching considerations subject to plasma dispersion are also examined.